LEADING FOR IMPACT: A SYSTEMATIC REVIEW OF WOMEN-LED SOCIAL ENTERPRISES AND THEIR ROLE IN ADVANCING GENDER EQUALITY AND SUSTAINABLE DEVELOPMENT - Sam-Sorungbe, Olusola; Duker, Daniel; Raj, Rahul; Boadi, Charles (International Journal of Small and Medium Enterprises, 2025)
This paper examines the contributions of women-led social enterprises (WLSEs) to gender equality and sustainable development, with particular attention to the interactions among leadership practices, social innovation, and institutional environments. Using a systematic literature review (SLR) methodology, the study analyses 52 peer-reviewed journal articles and institutional reports published between 2015 and 2025. The review follows the PRISMA 2020 protocol to ensure methodological rigour, transparency, and replicability. The findings indicate that WLSEs commonly adopt feminist and relational leadership approaches characterised by empathy, collaboration, and shared decision-making. These leadership practices foster inclusive organisational cultures and enhance empowerment outcomes for marginalised populations. The review further shows that WLSEs are significant drivers of social innovation, developing locally embedded and context-sensitive solutions to socio-economic challenges such as unemployment, financial exclusion, and environmental sustainability. However, despite their impact, WLSEs continue to face persistent institutional constraints, including restricted access to finance, gender-based bias, and underdeveloped or ambiguous regulatory frameworks. To advance theoretical understanding, the paper proposes the Leadership–Innovation–Institutional Nexus (LIIN) framework, which conceptualises how gendered leadership practices and social innovation interact with institutional structures to generate systemic change. The study argues that WLSEs function as agents of transformative development rather than marginal actors within the social economy. Policy implications include the need for gender-responsive financing mechanisms, supportive legal frameworks, and robust impact measurement systems to strengthen the long-term sustainability and scalability of women-led social enterprises. JEL Classification Codes: L26, J16, O35.